ANALISIS FAKTOR PENERIMAAN DAN PENGGUNAAN SOFTWARE ACCURATE DALAM PERSPEKTIF TECHNOLOGY ACCEPTANCE MODEL (Studi Empiris pada Mahasiswa Program Studi S1 Jurusan Akuntansi Fakultas Ekonomi Universitas Tadulako) - Rekka, Rendy; Totanan, Chalarce; Sudirman, Sudirman; Mayapada, Arung Gihna (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This study aims to analyze acceptance and usage factors of Accurate Software based on the perspective of technology acceptance model. These factors include perceived ease of use, perceived usefulness, and behavioral intention to use. We also add some external variables which are pressure to use and computer self efficacy. The data of this study are obtained from questionnaires and measured using Likert scale. The analysis method used in this study is partial least square (PLS). The sample is bachelor degree students of 2014, 2015, and 2016 batches in Accounting Department in Faculty of Economics in Tadulako University. The results of the study show that perceived ease to use, perceived usefulness, behavioral intention to use, pressure to use, and computer self efficacy have significant effect to actual usage of Accurate Software. The results of this study verify technology acceptance model.